Komáromi Csipkés György disputációjának peregrinációs kontextusa: De bis mortuis (A kétszer halottakról, 1656) - Kiss Farkas, Gábor (Studia Litteraria, 2026)
Upon returning from Utrecht, György Komáromi Csipkés organized a series of disputations at the Academy of Debrecen, where he attempted to recreate the university practices he had observed during his studies in the Low Countries. Of his four disputations published between1654 and 1656, my study analyses the De bis mortuis (On ose Who Have Died Twice) in detail, and I show that Ps-Augustinus’s work De miraculis Sacrae Scripturae, which examined the resurrections mentioned in the Holy Scriptures, played a major role in the argumentation of the De bis mortuis. From the context of the disputation’s publication, it is clear that Komáromi Csipkés, a student of Gijsbert Voetius, attacks his master’s opponent at the time, Samuel Maresius, in this treatise, and it was thanks to this that his text was later published several times in the Low Countries in Voetius’s circle.